Geometrical optic learning difficulties for Moroccan students during secondary/university transition - Naoual Nasser; El Mostapha El Khouzai; Abdallah Zahidi (Institute of Advanced Engineering and Science, 2021)
To remedy the difficulties encountered by Moroccan students in geometrical optics during the transition from secondary to higher education and for an efficient education system, we propose this study to investigate the causes of these difficulties as well as their impact on the quality of the secondary/university transition, and come up with a remediation device to overcome them. For this survey, we adopted a mixed method to collect both qualitative and quantitative data. The research tools used are semi-directive interviews with thirty high school and university teachers; questionnaires and exercises were administered to 120 of first year university students. The results of this study revealed the persistence of difficulties in geometrical optics and particularly in geometric construction whose origins are attributed to the misrepresentations and low prerequisites among students as well as a break in the curriculum and teaching methods during the transition from secondary to higher education.